Nonlinear multi-fields coupled model of magnetoelectric coefficient and sensitivity in bilayer ME sensor - Hao-Miao Zhou; Yun-Ning Wu; Yin-Qiu Hong; Yun Zhou; Jing Wei (AIP Advances, 2018)
Aiming to design magnetostrictive/piezoelectric asymmetric bilayer laminate structure that is commonly used in magnetoelectric (ME) sensor, a bilayer static nonlinear magneto-mechanical- electro-thermal coupled theoretical model which is about calculating ME coefficient and sensitivity is established. This model is based on the mechanical-electric linear constitutive relation of piezoelectric layer and one-dimension nonlinear thermal-magneto-mechanical constitutive relation of giant magnetostrictive material (GMM), in which the bending deformation caused by asymmetric structure has also been considered. The model shows universal applicability in the magnetostrictive/piezoelectric bilayer ME structure. In order to verify the validity of the model, magnetostrictive Terfenol-D and piezoelectric PZT are selected to constitute bilayer asymmetric ME composite structure sample, whose static ME coefficient is measured under different temperatures and bias magnetic fields. The model is degenerated to the ME coefficient model without stress, which shows a good predicted result being qualitatively and quantitatively consistent with experimental result confirming the validity of the model. Therefore, the nonlinear effects of pre-stress, bias magnetic field and environmental temperature, thickness ratio, as well as different piezoelectric materials on the ME coefficient and sensitivity were systematically investigated with our established model. The predicted result provides a roadway to improve static ME coefficient and sensitivity of devices by selecting different physic fields, materials, and thickness ratio for designing future ME sensors.